An Analysis of Process Type Used in News Item - Achmad Yudi Wahyudin (TEKNOSASTIK, 2016)
Since the educational curriculum for English subject in Indonesia is implemented around genres, news item has been one of the genres taught in secondary school in Indonesia. Understanding the authors’ points of view and intention will contribute significant implication for learning foreign language (FL). One of the ways of analyzing one’s experience in written language is by using systemic functional grammar (SFG) theory. Therefore, this article aims at providing SFG analysis of process type used on news item. The news item was selected from Jakarta Post, 2014 in which one article entitled 72% of Indonesian people agree with nuclear power plants was selected and analyzed by categorizing its experiential meaning (Gerot & Wignel, 1995). The analysis portrayed the dominance of verbal process existed in the article and it mainly indicate an effective news item.Since the educational curriculum for English subject in Indonesia is implemented around genres, news item has been one of the genres taught in secondary school in Indonesia. Understanding the authors’ points of view and intention will contribute significant implication for learning foreign language (FL). One of the ways of analyzing one’s experience in written language is by using systemic functional grammar (SFG) theory. Therefore, this article aims at providing SFG analysis of process type used on news item. The news item was selected from Jakarta Post, 2014 in which one article entitled 72% of Indonesian people agree with nuclear power plants was selected and analyzed by categorizing its experiential meaning (Gerot & Wignel, 1995). The analysis portrayed the dominance of verbal process existed in the article and it mainly indicate an effective news item.